Using anthropogenic raw materials in the process of synthesizing foam glass with heterogeneous microstructure - S. V. Fedosov; M. O. Bakanov; I. S. Grushko (Vestnik MGSU)
Introduction. Thermal insulation materials, including foam glass, are used to reduce heat losses in buildings. Foam glass has low thermal conductivity, high strength and environmental safety. Researches of scientists, including I.I. Kitaygorodsky and B.K. Demidovich, are aimed at controlling the process of foam glass synthesis and regulating the crystallization process. The cost reduction of foam glass is possible through the utilization of industrial waste.Materials and methods. The potential for reusing and obtaining foam glass is being studied using ash and slag waste from a power station in the Rostov region. The study of foam glass batch mixture includes preparation of raw materials, molding and firing. The research of the structure was conducted using an automatic diffractometer, micro-tomograph, and scanning electron microscope. Tests were carried out to assess the properties of foam glass specimens, such as thermal conducti-vity, strength, density, and load impact. The composition of raw materials for foam glass include broken glass, ash and slag mixture and Na2B4O7·10H2O. Foam glass synthesis was performed using anthracite, zirconium dioxide, chromium oxide, and magnesium oxide.Results. The research revealed the formation of crystalline phases in the amorphous foam glass framework. The presence of quartz, pyroxene, cristobalite, eskolaite, and wollastonite in foam glass composition was confirmed.Conclusions. Batch compositions and synthesis parameters were developed, leading to the production of nine modifications of foam glass with uniform porous structure and varying content of crystalline phases. Crystalline inclusions are evenly distributed. The role of crystallization centres is played by the crystalline phases present in the raw materials (in the composition of ash-and-slag mixture) and additional crystallization initiators (chromium oxide, zirconium dioxide and magnesium oxide). The conformity of foam glass properties to standard requirements was demonstrated.